Improving the Ductility of Mg–Gd–Y–Zr Alloy through Extrusion and a Following Rolling. Issue 6 (5th March 2018) - Wan, Yingchun; Liu, Chuming; Xiao, Hongchao; Gao, Yonghao; Jiang, Shunong; Chen, Zhiyong
Abstract : Ductility of the Mg–8Gd–3Y–0.4Zr alloy is improved through extrusion and a following rolling performed on the as‐cast alloy. Microstructure evolution, texture, and mechanical properties of the alloy are systematically investigated. The results indicate that the continuous‐cluster distributed β phase particles observed in the as‐cast alloy are fragmented and dissolved during the plastic deformation. Nearly random texture, improved ductility (by 60%), and strength (by 23%) are obtained. To uncover the formation mechanism of the texture, uniaxial compression on the alloys with and without homogenization (to obtain alloys without and with β phase) is performed. The microstructure characterization reveals that β phase impedes the grain boundary immigration, resulting in the nearly random texture, thereby improving the mechanical properties, especially the ductility of the alloy. Abstract : This work is aimed at improving the ductility of Mg–Gd–Y–Zr alloy by developing a novel processing method of combined extrusion and rolling. Nearly random texture, improved ductility (by 60%), and strength (by 23%) are obtained. The microstructure characterization reveals that β phase impeded the grain boundary immigration, resulting in the nearly random texture, thereby improving the mechanical properties, especially the ductility of the alloy.